CH Activation Generates Period‐Shortening Molecules That Target Cryptochrome in the Mammalian Circadian Clock1. (8th May 2015) - Oshima, Tsuyoshi; Yamanaka, Iori; Kumar, Anupriya; Yamaguchi, Junichiro; Nishiwaki‐Ohkawa, Taeko; Muto, Kei; Kawamura, Rika; Hirota, Tsuyoshi; Yagita, Kazuhiro; Irle, Stephan; Kay, Steve A.; Yoshimura, Takashi; et al.
Abstract The synthesis and functional analysis of KL001 derivatives, which are modulators of the mammalian circadian clock, are described. By using cutting‐edge CH activation chemistry, a focused library of KL001 derivatives was rapidly constructed, which enabled the identification of the critical sites on KL001 derivatives that induce a rhythm‐changing activity along with the components that trigger opposite modes of action. The first period‐shortening molecules that target the cryptochrome (CRY) were thus discovered. Detailed studies on the effects of these compounds on CRY stability implicate the existence of an as yet undiscovered regulatory mechanism.